Analysing the impact of FDI and Institutional Quality on Economic growth in South Asian: Panel ARDL APPROACH - Husnain, Muhammad Ali; Guo, Ping; Pan, Guoqin; Shaukat, Aqsa (iRASD Journal of Economics, 2023)
This study investigates the impact of institutional quality and foreign direct investment (FDI) on the economic growth of South Asia from 1996 to 2021. The analysis employs various statistical techniques, including panel unit root testing, panel cointegration testing, and Panel Autoregressive Distributive Lag (PARDL) models, to gain insights into the region's economic development. For finding the association between institutional quality, FDI, domestic investment and economic growth in South Asia, first tried to check the unit root problem in the selected series by employing the panel unit testing and results of these tests conclude that some variables are integrated at level while some other variables are integrated at the first difference, so for testing the cointegration or long-run relations among these variable the panel cointegration tests are employed and these tests conclude the long-run association among the variables. For checking the long and short-run impact of institutional quality, FDI, domestic investment and economic growth the panel ARDL test is employed. The results demonstrate the significant positive long and short-run impact of institutional quality, FDI, domestic investment on economic growth in the region of South Asia. These relationships demonstrate the persistent nature of interactions among these variables, emphasizing the importance of policies that promote strong institutions, attract foreign investments, and stimulate domestic capital formation to sustain regional economic growth. The study offers critical recommendations for South Asian countries to enhance their economic growth by focusing on the strengthening institutional quality, encouraging FDI, developing the special economic zones, promoting domestic investment, investing in the infrastructure and promoting regional economic integration. These recommendations offer a clear path for South Asian countries to achieve sustained economic growth by addressing the interplay between institutional quality, FDI and domestic investment dynamics. By implementing these measures, South Asia can secure lasting prosperity and enhance the well-being of its people in a rapidly evolving global economic landscape.